PTH-060 Better Care for IBD Biologic Patients: The Impact of A Multi-Disciplinary Virtual Clinic. (17th August 2016) - Eliadou, E; Reid, V; Kirkbride, M; Brooks, J; Birchall, F; Kemp, K; Levison, S
Abstract : Introduction: The IBD Standards, the Royal College of Physicians national biologic audit, and the NICE IBD quality standard (QS81) all aim to help deliver high quality, safe and appropriate clinical care to IBD patients throughout the UK. In line with these recommendations, and to improve and standardise the care of our IBD patients on biologic therapies we began a weekly multi-disciplinary (physicians, IBD nurses, and pharmacist) virtual biologics clinic (VBC). Here, the response to therapy is monitored (clinical scoring, well-being, laboratory results), the scheduling of investigations are coordinated, and the review and writing of prescriptions undertaken. Methods: We prospectively collected data from our VBC for 8 consecutive weeks. Changes to therapy on clinical grounds were noted, and the financial implications of these changes calculated. Calculations for IFX savings were based on an average dose of 300 mg per patient, plus infusion costs. The ordering of required investigations and the occurrence of adverse clinical events were recorded Results: In 8 weeks, 360 patient reviews were performed relating to 327 patients (IFX = 207, ADA = 79, VEDO = 41). Therapy was adjusted in 41/327 patients (12.5%). 5 stopped biologic therapy, 19 switched drug, 10 reduced and 7 increased the frequency of therapy. Net saving was £10, 928 at week 8 (>£65 K/annum). The coordinated prescribing of medication and pharmacy sign off improved the delivery of therapy and patient satisfaction. 23 colonoscopies, 9 MR scans, and 45 outpatient appointments to assess response to therapy at 3 or 12 months and clinical input were scheduled from the VBC. The ordering of anti-TNF drug and antibody levels solely through the VBC reduced any duplication of requests and ensured the review and actioning of results. 5 complications were highlighted (recurrent infections; 2 requiring surgery; cancer; severe IBD flare requiring hospitalisation). Conclusion: The introduction of a multi-disciplinary VBC has altered the management of 41/327 patients (12.5%) based on clinical findings and the results of investigations. Significant financial savings (£65 K per annum), the streamlining of prescribing, and superior patient monitoring have helped to improve the quality and safety of care provided. With better monitoring, care, NICE compliance, and financial prudence, this will help to sustain or service and practices. Disclosure of Interest: None Declared